Strategic Assets Exploring The Influence Of Human Capital, Organizations, And Relationships For Performance Advantage (Case Study Of Cimahi City Bappenda) - Riadi, Farid; Coenraad, Dhea Perdana (Transforma Jurnal Manajemen, 2024)
Human resource management (HR) and organizational performance are the focus of this study in the context of government sector management in Indonesia. This study aims to identify and analyze the influence of human resource capital, organizational capital, and relationship capital on performance. The research method used is quantitative research with path analysis techniques. The results of the analysis show that the three independent variables have a significant influence on employee performance, with a total contribution of 87.80%. Human resource capital has the most dominant impact, followed by organizational capital and relationship capital. Although relationship capital has a significant impact, it still requires support from high human resource capital and organizational capital. The implication of this study is the importance of human resource management in achieving the success of government organizations in the future, with a focus on the management of State Civil Apparatus (ASN) and the challenges faced such as disciplinary violations and abuse of authority. In addition, this study also highlights the importance of organizational capital and relationship capital in improving overall organizational performance and building mutually beneficial relationships with stakeholders. With a deep understanding of the complexity of the relationships between the variables studied, this study provides important insights for decision makers in designing human resource management strategies and stakeholder relationship management to achieve organizational success in the future.